2015
DOI: 10.1007/s13402-015-0238-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cytokeratin-7 mRNA expression in peripheral whole blood of advanced lung adenocarcinoma patients

Abstract: Our data show that KRT7 mRNA expression measured by RT-qPCR serves as a sensitive approach for the molecular detection of KRT7-positive CTC-resembling A549 cells in peripheral whole blood. The KRT7 mRNA levels measured were not significantly associated with the response to chemotherapy or the survival of patients with advanced lung AC. Additional studies are required to establish the possible clinical significance of KRT7 mRNA expression in whole blood after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Since metastasis is one of the most crucial factors determining the survival of cancer patients, ample attempts have been made to identify key molecular mediators that control metastasis. Nonsmall cell lung cancer (NSCLC) is a highly metastatic malignancy, and the disease is estimated to be the leading cause of cancer-related death [4][5][6][7][8]. The endogenous gas nitric oxide (NO) is known to play a role in the progression of different types of cancer [9] and it has been found that the expression of several forms of NO synthases (NOSs) is strongly upregulated in, among others, NSCLC cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since metastasis is one of the most crucial factors determining the survival of cancer patients, ample attempts have been made to identify key molecular mediators that control metastasis. Nonsmall cell lung cancer (NSCLC) is a highly metastatic malignancy, and the disease is estimated to be the leading cause of cancer-related death [4][5][6][7][8]. The endogenous gas nitric oxide (NO) is known to play a role in the progression of different types of cancer [9] and it has been found that the expression of several forms of NO synthases (NOSs) is strongly upregulated in, among others, NSCLC cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…In that study, however, they took 20 mL of blood from 43 patients with NSCLC at various stages of disease (56% stage IV) using, after the negative selection, immunofluorescence, a method with a poor sensitivity. In another study in NSCLC patients, CTCs were highlighted by CK7 mRNA expression measured by RT-PCR; there was not a significant association between CK7 mRNA levels and the response to chemotherapy or the survival [ 45 ]. Based on our data, we think this contrasting result is due to the use of only one epithelial marker and so it emphasizes how the expression of mesenchymal markers in combination with epithelial ones can significantly improve the CTCs detection.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from tumor and normal tissue samples was extracted using a miRNeasy Mini Kit (Qiagen) according to the manufacturer's instructions. RNA from peripheral whole blood samples was extracted using a PAXgene Blood miRNA Kit (PreAnalytiX) as previously described [ 48 ]. Briefly, all RNA samples were treated with RNase-free DNase (Qiagen) and reverse transcribed to cDNA using high-capacity cDNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%